APOE is a correlate of phenotypic heterogeneity in Alzheimer disease in a national cohort. (11th February 2020) - Weintraub, Sandra; Teylan, Merilee; Rader, Benjamin; Chan, Kwun C.G.; Bollenbeck, Mark; Kukull, Walter A.; Coventry, Christina; Rogalski, Emily; Bigio, Eileen; Mesulam, M.-Marsel
Abstract : Objective: To compare the proportion of APOE ε4 genotype carriers in aphasic vs amnestic variants of Alzheimer disease (AD). Method: The proportion of APOE ε4 carriers was compared among the following 3 groups: (1) 42 patients with primary progressive aphasia (PPA) and AD pathology (PPA/AD) enrolled in the Northwestern Alzheimer Disease Center Clinical Core; (2) 1, 418 patients with autopsy-confirmed AD and amnestic dementia of the Alzheimer type (DAT/AD); and (3) 2, 608 cognitively normal controls (NC). The latter 2 groups were compiled from the National Alzheimer Coordinating Center database. Logistic regression models analyzed the relationship between groups and APOE ε4 carrier status, adjusting for age at onset and sex as needed. Results: Using NC as the reference and adjusting for sex and age, the DAT/AD group was 3.97 times more likely to be APOE ε4 carriers. Adjusting for sex and age at symptom onset, the DAT/AD group was 2.46 times as likely to be carriers compared to PPA/AD. There was no significant difference in the proportion of APOE ε4 carriers for PPA/AD compared to NC. PPA subtypes included 24 logopenic, 10 agrammatic nonfluent, and 8 either mixed (n = 5) or too severe (n = 3) to subtype. The proportion of carriers and noncarriers was similar for logopenic and agrammatic subtypes, both having fewer carriers. Conclusion: The proportion of APOE ε4 carriers was elevated in amnestic but not aphasic manifestations of AD. These results suggest that APOE ε4 is an anatomically selective risk factor that preferentially increases the vulnerability to AD pathology of memory-related medial temporal areas rather than language-related neocortices.